Insurance in the system of social risks management. (Journal of Economic Research & Business Administration, 2016)
The article analyzes the category of “social risk” from different perspectives, the author is considering the interpretation of the leading authors in the field of social security and makes some definite conclusions. Social risks are risks associated with the life of a person in the state and society. Under conditions of objective existence of social risk and the associated financial, moral and spiritual losses, there is a need for developing a mechanism that would allow the best of all possible ways to consider the risk when making and implementing decisions in life. One of such mechanisms is social insurance. Common characteristics and types of social risk as a special kind of risks are identified. The role of social insurance as the main risks of the social risk management is defined; the major insurance functions in the management of social risks are identified The author has analyzed the main social risks, enshrined in laws in the Republic of Kazakhstan. The dynamics of social payments and the number of recipients of such risks as disablement (loss of ability to work), loss of breadwinner, loss of job, loss of income due to pregnancy and childbirth, adoption (adoption) of a newborn child (children), the loss of income due to childcare attaining the age of one year. The role of the State Social Insurance Fund in the management of social risks has been analyzed.
Keywords: social risk; social insurance; social security; unemployment; social payments; disablement; the State Social Insurance Fund.